Phase-Sensitive Optical Time-Domain Reflectometer Based on a 120°-Phase-Difference Michelson Interferometer - 曹玉龙 杨飞 徐丹 叶青 蔡海文 方祖捷 (Chinese physics letters, 2016)
A phase-sensitive optical time domain reflectometer （φ-OTDR） based on a 120°-phase-difference Michelson in- terferometer is proposed. The Michelson interferometer with arm difference of 4m is used to test the phase difference between the Rayleigh scattering from two sections of the fiber. A new demodulation method called the inverse transmission matrix demodulation scheme is utilized to demodulate the distributed phase from the backward scattering along the long fiber, The experimental results show that the 120°-phase-difference inter- ferometer φ-OTDR can detect the phase along the 3km fiber, and the acoustic signal within the whole human hearing range of 20 Hz-20 kHz is reproduced accurately and quickly.